Klausula Boiler Plate dalam Pembuatan Kontrak Dagang Internasional: Boilerplate Clauses in Making International Trade Contracts - Widhiyanti, Hanif Nur (Faculty of Law, Universitas Brawijaya, 2021)
In an international trade contract, the parties are bound by different legal provisions, different languages and also different customs and cultures. This condition creates a big risk in implementing the substance of the contract. To anticipate this risk, there are several steps that can be taken by the parties in terms of arranging and creating the contents of their contracts. This article will discuss the part of the contract that is often regulated in international trade contracts, called the boiler plate clause. This article is the result of normative research, both related to national legal norms, namely the Civil Code, Uniform law and examples of international trade contracts. A contract is a mechanism for expressing all the wishes of the parties agreed to by other parties. In current developments, contract clauses are no longer just the essentials of the agreement. There are other clauses which have the function of further clarifying how the contract must be interpreted and as an effort to cover all opportunities for contract failure, including what are called boilerplate clauses. In the practice of making international trade contracts, there are several substances that need to be regulated in boilerplate clauses, including choice of law provisions, choice of forum provisions, language provisions, severability provisions, integration provisions, notices provisions, force majeure provisions, duration of contract provisions, obligation after termination provision.